2014
DOI: 10.1074/jbc.m114.604264
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cellobiohydrolase (Cel7A) Variants with Lowered Substrate Affinity

Abstract: Background:To elucidate the rate-determining steps of cellobiohydrolase Cel7A from T. reesei, variants with lower substrate affinity were designed. Results: Mutant (W38A) had reduced substrate affinity but a 2-fold increase in the maximum quasi-steady-state rate. Conclusion: Dissociation of stalled TrCel7A is the rate-limiting step in the initial phase of hydrolysis. Significance: This work offers a new perspective for the design of faster cellulases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
86
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(115 citation statements)
references
References 66 publications
(102 reference statements)
19
86
1
Order By: Relevance
“…If CBM-cellulose interactions indeed contribute to a slower dissociation, higher maximal rates for the one-domain variants could reflect faster dissociation of unproductively bound enzyme (and hence earlier recruitment for new attacks). This interpretation parallels a recent study where the substrate affinity of Hj CBM was lowered by the mutation W38A in the catalytic domain (25). Kinetic analysis of this variant at 25°C showed a 4-fold increase in p K m and a 2-fold increase in p V max compared with the wild type.…”
Section: Discussionsupporting
confidence: 89%
“…If CBM-cellulose interactions indeed contribute to a slower dissociation, higher maximal rates for the one-domain variants could reflect faster dissociation of unproductively bound enzyme (and hence earlier recruitment for new attacks). This interpretation parallels a recent study where the substrate affinity of Hj CBM was lowered by the mutation W38A in the catalytic domain (25). Kinetic analysis of this variant at 25°C showed a 4-fold increase in p K m and a 2-fold increase in p V max compared with the wild type.…”
Section: Discussionsupporting
confidence: 89%
“…Similar trends have also been observed with processivity-deficient variants of the other S. marcescens chitinase, ChiB (10). Studies of TrCel7A variants with lower processivity also revealed higher activity compared with the wild type enzyme on amorphous cellulose (12,43). Thus, the negative effect of processivity (slow off-rate) in hydrolysis of amorphous substrates seems to be a general feature among glycoside hydrolases evolved to degrade recalcitrant polysaccharides (7,43).…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, the activity on crystalline chitin was poor, indicating the importance of processivity in the crystalline substrate degradation (7,11). The reduction of processivity upon changing Trp to Ala in substrate-binding sites has been demonstrated also for fungal (12) as well as bacterial cellulases (13)(14)(15)(16).…”
mentioning
confidence: 99%
See 2 more Smart Citations